Impact of Attending Prenatal Yoga Classes on Prepartum Maternal Mental Health : A Quasi-Experimental StudyI: Prenatal Yoga Classes on Maternal Mental Health - Fitri, Imelda; Herlina, Sara; Nasution, Itto Nesyia; Fridons, Aurelia; Utami, Riski Dwi (Indonesian Journal of Obstetrics and Gynecology, 2025)
INTRODUCTION Anxiety from the imagination of childbirth pain and fear of childbirth in pregnant mothers. Fear of childbirth has been associated with prolonged labor, childbirth complications that increased postpartum depression. OBJECTIVE : This study aimed to determine the effect of prenatal classes on mental health. METHODS The research design was a quasi-experiment of two groups with pre-test and post-test design. The sample was pregnant women who met the inclusion and exclusion criteria. A total of 106 participants were divided into two groups: intervention, and control group. The research instrument was a questionnaire. The ANOVA test was used to analyze the data. RESULT The average mental health score of the intervention group was higher (84.04) than that of the control group (67.32), with a p-value <0.001. CONCLUSIONS This study concludes that yoga prenatal classes improve positive mental health status Keywords: Pregnant Women; Yoga Prenatal Class; Mental Health INTRODUCTION Anxiety from the imagination of childbirth pain and fear of childbirth in pregnant mothers. Fear of childbirth has been associated with prolonged labor, childbirth complications that increased postpartum depression. OBJECTIVE : This study aimed to determine the effect of prenatal classes on mental health. METHODS The research design was a quasi-experiment of two groups with pre-test and post-test design. The sample was pregnant women who met the inclusion and exclusion criteria. A total of 106 participants were divided into two groups: intervention, and control group. The research instrument was a questionnaire. The ANOVA test was used to analyze the data. RESULT The average mental health score of the intervention group was higher (84.04) than that of the control group (67.32), with a p-value <0.001. CONCLUSIONS This study concludes that yoga prenatal classes improve positive mental health status Keywords: Pregnant Women; Yoga Prenatal Class; Mental Health